Neuronal correlates of the dominant role of GABAergic transmission in the developing mouse locomotor circuitry. (26th March 2013) - Ziskind‐Conhaim, Lea
Abstract : GABA and glycine are the primary fast inhibitory neurotransmitters in the mammalian spinal cord, but they differ in their regulatory functions, balancing neuronal excitation in the locomotor circuitry in the mammalian spinal cord. This review focuses on the unique role of GABAergic transmission during the assembly of the locomotor circuitry, from early embryonic stages when GABAA receptor–activated membrane depolarizations increase network excitation, to the period of early postnatal development, when GABAergic inhibition plays a primary role in coordinating the patterns of locomotor‐like motor activity. To gain insight into the mechanisms that underlie the dominant contribution of GABAergic transmission to network activity during that period, we examined the morphological and electrophysiological properties of a subpopulation of GABAergic commissural interneurons that fit well with their putative function as integrated components of the rhythm‐coordinating networks in the mouse spinal cord.